PENGARUH CITA RASA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK PAROTI DI ALFAMART COMAL KABUPATEN PEMALANG - Kharisma Nawang Sigit; Fitri Awan Arif Firmansyah (Nusantara Hasana Journal, 2021)
This study aims to determine whether there is an influence of taste on purchasing decisions for Paroti products and to determine product quality on purchasing decisions for Paroti products at Alfamart Comal, Pemalang Regency. The sample in this study are consumers who buy Paroti products. The number of samples is 87 respondents. Sampling using Simple Random Sampling technique. Collecting data in this study using a questionnaire that has been tested and meets the requirements of validity and reliability. The research uses quantitative research methods and data analysis methods using multiple linear regression. The results of this study indicate that the variable, Taste partially and significantly influences the purchasing decision of Paroti products, while the quality of the product has no significant effect on the decision to purchase Paroti products at Alfamart Comal Pemalang Regency.